Book Review: Thomas Risse, A Community of Europeans? Transnational Identities and Public Spheres - Scott Nicholas Romaniuk (Romanian Journal of European Affairs)
This book represents a multi-faceted and multi-dimensional exploration of Europe as an institutional and social conception. It systematically links understanding of the Europeanization of identities and public spheres with citizenship, nationalism, community and communication, EU (European Union) enlargement, institution-building, and European democracy and politicization. As a hallmark of insightful and dynamic scholarship, Risse’s work draws inspiration from a variety of societal levels, including some of the most critical players in European political life today, and highly-praised and well-known political philosophers, and policymakers.